Alternative Sensing for State-of-Charge Estimation of Latent Heat Thermal Energy Storage - James Wilson; Robert J. Barthorpe; Furkan Terzioglu (Energies)
Thermal energy storage (TES) is likely to play a significant role in the decarbonisation of domestic heat, allowing consumers to shift their energy consumption away from peak demand periods and reducing overall strain on the grid. Phase change materials (PCMs) are a promising option for TES, in which energy can be stored in the latent heat of the melting of the PCM; these offer greater storage densities than sensible heat TES and have the benefit of releasing stored heat at a consistent temperature (the crystallisation temperature of the PCM). One of the key difficulties for PCM-based TES is state of charge (SoC) estimation (the estimation of the proportion of energy stored in the TES unit up to its maximum capacity), particularly during idle periods while the unit is storing heat. SoC estimation is key to the implementation of TES, as it enables the effective control of the units. The use of a resonator within the PCM for SoC estimation could potentially provide a global estimate of the SoC, since the resonator passes through the full depth of the PCM in the unit. The SoC could be inferred by measuring the vibrational response of the resonator under excitation, which varies depending on the melt state of the PCM. This paper presents findings from a test rig investigating this proposal, including discussions on the features required from the resonator response for SoC inference.